Perancangan Kursi dan Meja Penjahit Yang Ergonomis untuk Meningkatkan Produktivitas Kerja - Hidayatullah, Anung Andi; Mauluddin, Yusuf; Utama, Deni Tri (Jurnal Kalibrasi, 2024)
At Thexild Apparel Convection, there is a problem that workers often experience complaints of Musculoskeletal (Muscle) pain while working, which causes workers to often ask for additional time off because they feel this pain, causing work productivity to decrease. The aim of this research is to design ergonomic tailoring chairs and tables to increase work productivity. The methods used in this research are the Nordic Body Map to identify pain complaints, EFD (Ergonomic Function Deployment) and Anthropometrics are used to design products, and the RULA (Rapid Upper Limb Assessment) Method is used to analyze product design results. The results of this research resulted in an ergonomic design of tailor's chairs and tables by applying a stabilizer feature where the position of the chairs and tailor's tables could be adjusted to reduce complaints of musculoskeletal (muscle) pain felt by workers. Then, making the tailor's table multi-functional from being usually only used for sewing, this design is also made for cutting work, patterning raw materials to be sewn, then also adds a place to store raw materials to be sewn and those that have already been sewn. Therefore, workers will be more productive and will not need to ask for additional rest time, which will increase work productivity by 45.33% from before.